1994
DOI: 10.1346/ccmn.1994.0420310
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Synthetic Birnessite as Affected by pH and Manganese Concentration

Abstract: AImtract--The amount of Mn 2+ adsorbed or removed from solution by birnessite is several times greater than its reported cation exchange capacity. Extractability of the sorbed Mn 2+ decreases with aging. It is uncertain whether the sorbed Mn 2+ is oxidized on the surface or incorporated into the structure of birnessite. Using X-ray powder diffractometry and transmission electron microscopy, a study was conducted to examine the mineralogical alteration of birnessite after treatment with various concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 20 publications
5
65
1
Order By: Relevance
“…Partial dehydration of buserite leads to the formation of 7 Å birnessite with a single layer of H 2 O molecules and various interlayer cations Burns 1977, 1978;Chukhrov et al 1978Chukhrov et al , 1989Cornell and Giovanoli 1988). Buserite and birnessite have remarkable cation exchange (Healy et al 1966;Murray 1974;Balistrieri and Murray 1982;Stumm 1992;Le Goff et al 1996), sorption (Gray and Malati 1979;Catts and Langmuir 1986;Paterson et al 1994;Tu et al 1994;Appelo and Postma 1999), and redox properties (Oscarson et al 1983;Stone and Morgan 1984;Stone and Ulrich 1989;Manceau and Charlet 1992;Bidoglio et al 1993;Silvester et al 1995;Manceau et al 1997;Pizzigallo et al 1998;Daus et al 2000;Nico and Zasoski 2000;Chorover and Amistadi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Partial dehydration of buserite leads to the formation of 7 Å birnessite with a single layer of H 2 O molecules and various interlayer cations Burns 1977, 1978;Chukhrov et al 1978Chukhrov et al , 1989Cornell and Giovanoli 1988). Buserite and birnessite have remarkable cation exchange (Healy et al 1966;Murray 1974;Balistrieri and Murray 1982;Stumm 1992;Le Goff et al 1996), sorption (Gray and Malati 1979;Catts and Langmuir 1986;Paterson et al 1994;Tu et al 1994;Appelo and Postma 1999), and redox properties (Oscarson et al 1983;Stone and Morgan 1984;Stone and Ulrich 1989;Manceau and Charlet 1992;Bidoglio et al 1993;Silvester et al 1995;Manceau et al 1997;Pizzigallo et al 1998;Daus et al 2000;Nico and Zasoski 2000;Chorover and Amistadi 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining unoxidized Co 2+ is adsorbed above or below the vacant sites . As Mn 2+ is easily oxidized by birnessite (Tu et al 1994) and as the radius of Mn 3+ (0.066 nm) is close to that of Co 3+ (0.063 nm; Pauling 1960), it is reasonable to suggest that the oxidation of Mn 2+ to Mn 3+ on birnessite is similar to the oxidation of Co 2+ adsorbed on buserite. Therefore, the first and third mechanisms are both possible.…”
Section: Discussionmentioning
confidence: 99%
“…Mn 2+ can be oxidized to Mn 3+ by birnessite (Tu et al 1994), and the radius of Mn 3+ (0.066 nm) is close to that of Co 3+ (0.063 nm; Pauling 1960), suggesting that the oxidation of Mn 2+ to Mn 3+ on birnessite is similar to that of Co 2+ oxidation to Co 3+ on buserite, leading to a decrease in vacant Mn sites in birnessite.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…R-MnO 2 was formed with transformation of birnessite after adsorbing Mn 2+ at pH 2.4, but XRD results identified that the product was a mixture of nsutite and ramsdellite. 17 Rietveld refinement technique and oriented single-crystal IR absorption spectra were used to characterize the ramsdellite, which was found to be easily distorted to groutite, α-MnOOH. 18,19 Rossouw et al prepared pure R-MnO 2 with digestion of spinel LiMn 2 O 4 or Li 2 Mn 4 O 9 in moderately concentrated sulfuric acid solution at 95 ℃ for 24 h. However, the preparation process was multistep, complicated and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%